Remote laboratories: enhancing accredited engineering degree programs - Lindsay, Euan; Stumpers, B. (Engineers Australia, 2011)
Remote laboratories have been subjected to considerable scrutiny, as to their place in educational programs, since their original use in the early 90’s. Since this time they have been the focus of academic research, and subsequent reviews, which show that they have potential advantages over traditional laboratories when correctly used. While these advantages are generally understood and agreed on, there is still some concern as to the impact they might have on the accreditation of existing programs. The body responsible for accreditation in Australia, Engineers Australia, takes a holistic approach to the accreditation of academic programs. In order to receive accreditation a program must satisfy all criteria within Engineers Australia’s categorical assessment. This paper uses a criterion-by-criterion analysis to show that remote laboratories have no negative impact on any of these criteria and in some cases actually have a positive impact. Therefore the accreditation of academic programs containing remote laboratories are just as likely to have a positive outcome, assuming the laboratory is designed to embody the guiding pedagogical principles of the program in question.